Efektivitas Pemungutan Pajak Bumi dan Bangunan Perdesaan Perkotaan (PBB-P2) Dalam Meningkatkan Penerimaan Pada Unit Pelayanan Pemungutan Pajak Daerah (UPPPD) Kecamatan Ciracas Jakarta Timur Tahun 2020-2023 - Ambarwati, Ambarwati; Dewi, Maharani Cantrika (Jurnal Ilmu Administrasi Publik, 2024)
The phenomenon of the study is that there are changes due to significant economic impacts, followed by a process of economic recovery. 2021 was the year with the lowest realization compared to the target. The year 2023 showed a strong recovery with realization exceeding the target. This study aims to resolve the effectiveness of the settlement of urban rural land and building tax (PBB-P2) in increasing revenue at the local tax collection service unit (UPPPD) in 2020-2023 and to find out the obstacles and solutions in collecting PBB-P2. This research uses duncan`s theory. The research method is descriptive qualitative, the data collection techniques used are observation, interviews, documentation, and triangulation. Interviews were conducted with data collection section staff, billing section staff, academics and taxpayers, the results showed that PBB-P2 collection has been running effectively, as evidenced by the existing revenue data reaching the predetermined target. However, not all managed to reach the target due to declining economic factors. This happens because of the lack of public awareness, as well as the obstacles that occur, namely the limited knowledge of taxpayers, especially in accessing technology, the vagueness and incompleteness of tax object data, and the accessibility of the Ciracas District Regional Tax Collection Service Unit (UPPPD) office location that is difficult to reach by taxpayers, inadequate transportation infrastructure. And the solution is to conduct socialization activities for urban rural land and building tax collection (PBB-P2), improve services at the Regional Tax Collection Service Unit (UPPPD) office and reclamation programs with discounts.